Detection and Analysis - Ramsden, E. N. (Cheltenham : Stanley Thornes, 1996)
Written in the author's popular and successful style, this book is concise, student-friendly and illustrated with diagrams, charts and tables wherever possible. It is ideal for revision and self-assessment.
Keywords: Chemistry, Analytic -- Examinations -- Study guides; Popular Science